Employees’ Subjective Valuations of Their Stock Options: Evidence on the Distribution of Valuations and the Use of Simple Anchors* - Farrell, Anne M.; Krische, Susan D.; Sedatole, Karen L. (Contemporary Accounting Research, 2011)
Although prior research presents employees’ subjective valuations of their stock options as being either below or above firms’ opportunity cost of issuing options, we examine subjective valuations in terms of their distribution around cost. We argue that variation of subjective valuations within this distribution is at least partly attributable to employees’ failure to fully incorporate the time-value component of options and their tendency to, instead, anchor on readily-available components of option value. Using both “real-world” and experiment data, we show that a significant proportion of both employees (30 percent) and experiment participants (47 percent) anchor on three readily-available values, two of which lie below cost (zero value, intrinsic value) and one of which lies above (stock price). We further find that a stock option education program aimed at mitigating the tendency to disregard the time-value component leads to a significant change in valuations (in terms of both median values and dispersion) and lower reliance on simple anchors. Education in the form of cognitive feedback has a greater effect on subjective valuations of additional options with differing characteristics as compared to education in the form of outcome feedback on the original option holdings.